COMPARISON OF EFFICACY OF SPINAL ANAESTHESIA AND SUB-FASCIAL LOCAL ANAESTHETIC INGUINAL FIELD BLOCK FOR OPEN INGUINAL HERNIA REPAIR-A SINGLE INSTITUTIONAL EXPERIENCE - Shafique, Natasha; Rashid, Haroon Ur; Raja, Muhammad Ijaz; Saeed, Mohammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: The use of local anaesthetic for open inguinal hernia surgery has long been restricted to specialist centres. This study aimed to compare the efficacy of spinal anaesthesia and sub-fascial local anaesthetic (LA) for performing open hernia repair and at the same time provide better post op pain relief and early mobilization. Methods: In this randomized clinical trial, 62 male patients aged 16-72 were randomly allocated to two groups. Group A received mixture of 20ml 0.5% bupivacain,20ml 2% lignocaine with adrenaline, 20ml normal saline (N/S), 3 ml NaHCO3 sub-fascially for Local anaesthetic (LA) inguinal field block, while Group B received Spinal Anaesthesia (SA) with 0.5%Bupivacaine. Comparison was made in terms of Visual Analogue Score (VAS) recorded intra-operatively at 0 and 30 minutes and post operatively at 2, 4 and 12 hours at rest and on movement. Need for rescue analgesia and total analgesic consumption in both groups were calculated. Interval to pain free ambulation as well as procedural and anaesthesia related complications were compared. Results: Mean VAS in the intraoperative period were significantly high in Group A (p-value 0.011) at the start of operation and at 30 minutes (p-value <0.001). However, it did not correlate with patient satisfaction as 90% of patients in Group A successfully underwent the procedure without need for supplemental analgesia. VAS scores at rest and on movement/cough were comparable in the post op period at 2, 4 and 12 hours in both groups. Interval to pain free ambulation was significantly low in Group A (p-value 0.0012). Conclusion: Sub facial LA inguinal field block provides effective anaesthesia with optimum post op analgesia, prompt recovery and fewer systemic side effects compared to SA and can safely be used for routine open inguinal hernia surgery. Keywords: Spinal Anaesthesia, Sub-Fascial local anaesthetic inguinal field block, open inguinal hernia repair, efficacy